Frogs of the United States and Canada, 2-vol. set - Dodd, C. Kenneth (Book collections on Project MUSE., 2013)
With many frog populations declining or disappearing, and with developmental malformations and disease afflicting others, scientists, conservationists, and concerned citizens need to be aware of the status of various frog species. This is a comprehensive resource for those trying to protect amphibians as well as for researchers and wildlife managers who study biodiversity. From acrobatic tree frogs to terrestrial toads, the author offers a synthesis of the biology, behavior, and conservation of frogs in North America.